The Relationship Between High Folate Food Intake with Breast Cancer in Premenopausal Women and Views According to Islam - Rizky Carita Putri Toengkagie, Annisa; Kuntarti Heruyanto, Retno; Arsyad, Muhammad (Jurnal Indonesia Sosial Sains, 2023)
Breast cancer is a non-infectious malignancy that can attack ductal or lobular epithelial cells in the glandular tissue of the breast. Breast cancer is one of the most common types of cancer in Indonesia and the world. This study aims to determine the level of folate consumption in premenopausal women and its association with breast cancer. The research design used was case control. Premenopausal women's folate consumption levels from both groups were obtained using the Semi-quantitative Food Frequency Questionnaire. The results of the study were obtained from 76 respondents, the majority of respondents were >41 years old when diagnosed with breast cancer (45.8%). Based on the results of the variable analysis, it was found that a total of 5 respondents smoked. Respondents who smoked were more in the control group with 4 respondents (80%) compared to the breast cancer group which only amounted to 1 respondent (20%). Based on the results of the analysis, it was found that only one respondent consumed alcohol and came from the breast cancer group. History of cancer in the family was found more in the breast cancer group, namely 17 respondents (73.9%). Based on these results, it can be concluded that a family history of cancer is a significant factor (p value <0.05). Based on the results of an analysis of folic acid consumption by breast cancer and control groups, it was shown that in the breast cancer group, respondents with low consumption of folate were more, namely 22 respondents (55%), with a difference of 10%. Whereas in the control respondents, there were more respondents in the high consumption category, namely 16 respondents (44.4%) with a difference of 11.2%. In this study, it was found that there was no significant relationship between intake of foods high in folate and the incidence of breast cancer in premenopausal women (p value > 0.05).